MELESTARIKAN BAHASA SASAK MELALUI CERITA-CERITA RAKYAT PADA LINGKUNGAN KELUARGA DAN SEKOLAH UNTUK ANAK USIA DINI YANG DITINJAU DARI PENDEKATAN SOSIOLINGUISTIK - Baiq Yulia Kurnia Wahidah (LPPM Institut Pendidikan Nusantara Global, 2020)
This research purpose was to describe linguistic data related to language preservation planning in children through family and school environments in folklore. The method of this research was a descriptive qualitative which describes the influence of using folk tales to preserve the Sasak language. In the analysis, the data was in the form of linguistic data that contains moral values that can be taught to children through folklore and can strengthen Sasak language porting. The result of this research was the factors that can influence the training of the Sasak language can be found through folk stories. Children can also practice Sasak languages starting from sitting in Kindergarten so that the Sasak language doesn't become extinct.